2014
DOI: 10.5505/tjtes.2014.54938
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a hemostatic agent in anticoagulant drug-induced rat bleeding model

Abstract: BACKGROUND:Bleeding is a major problem in warfarin pretreated patients who need emergency surgical procedures. APH is a hemostatic agent with ultra-hydrophilic and particulate properties. This study aimed to evaluate the in vivo hemostatic effect of APH in rats pretreated with warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…When new drugs are initially applied, researchers tend to pay more attention to their effects on the prevention of thrombus formation. However, an increasing number of studies have found that these drugs are associated with a higher incidence of bleeding [16, 17]. Therefore, we aimed to comprehensively analyse the thromboprophylactic drugs that are used to prevent thrombosis and reduce bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…When new drugs are initially applied, researchers tend to pay more attention to their effects on the prevention of thrombus formation. However, an increasing number of studies have found that these drugs are associated with a higher incidence of bleeding [16, 17]. Therefore, we aimed to comprehensively analyse the thromboprophylactic drugs that are used to prevent thrombosis and reduce bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…Sönmez et al . reported that APH which is a hemostatic agent with ultrahydrophilic and particulate properties has an effective hemostatic property in rats pretreated or nonpretreated with anticoagulants . It was found that the bleeding time in groups pretreated with warfarin and in the saline administered subgroup were 3.61 and 2.40 min, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…If location of the bleeding is unknown, those in the form of a leakage, pressure method or vasoconstrictor agents can be used. Nowadays, hemostatic agents are used in a wide-range of operation and have been reported by many researchers as effective in controlling bleeding 7 .…”
Section: Discussionmentioning
confidence: 99%